Modulation of the Relationship Between External Knee Adduction Moments and Medial Joint Contact Forces Across Subjects and Activities. Issue 5 (May 2014) - Trepczynski, Adam; Kutzner, Ines; Bergmann, Georg; Taylor, William R.; Heller, Markus O.
<x xml:space="preserve">Abstract</x> Objective The external knee adduction moment (EAM) is often considered a surrogate measure of the distribution of loads across the tibiofemoral joint during walking. This study was undertaken to quantify the relationship between the EAM and directly measured medial tibiofemoral contact forces (Fmed) in a sample of subjects across a spectrum of activities. Methods The EAM for 9 patients who underwent total knee replacement was calculated using inverse dynamics analysis, while telemetric implants provided Fmed for multiple repetitions of 10 activities, including walking, stair negotiation, sit‐to‐stand activities, and squatting. The effects of the factors "subject" and "activity" on the relationships between Fmed and EAM were quantified using mixed‐effects regression analyses in terms of the root mean square error (RMSE) and the slope of the regression. Results Across subjects and activities a good correlation between peak EAM and Fmed values was observed, with an overall R2 value of 0.88. However, the slope of the linear regressions varied between subjects by up to a factor of 2. At peak EAM and Fmed, the RMSE of the regression across all subjects was 35% body weight (%BW), while the maximum error was 127 %BW. Conclusion The relationship between EAM and Fmed is generally good but varies considerably across subjects and activities. These findings emphasize the limitation of relying solely on the EAM to infer medial joint loading when excessive directed cocontraction of muscles exists and call for further investigations into the soft tissue–related mechanisms that modulate the internal forces at the knee.